2019
DOI: 10.1088/2631-7990/ab22a9
|View full text |Cite
|
Sign up to set email alerts
|

Developments and perspectives on the precision forming processes for ultra-large size integrated components

Abstract: In order to meet the requirements of high reliability, long-lifetime and lightweight in a new generation of aerospace, aviation, high-speed train, and energy power equipment, integrated components are urgently needed to replace traditional multi-piece, welded components. The applications of integrated components involve in a series of large-size, complex-shaped, high-performance components made of difficult-to-deform materials, which present a huge challenge for forming ultra-large size integrated components. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…With high strength-to-weight ratio, excellent fracture toughness, and good corrosion resistance [1][2][3] , aluminum alloys have been widely used in the manufacture of curved shell in aviation, aerospace, automotive, and marine fields, such as the bottom of launch vehicle fuel tanks, aircraft skins, body coverings of automotive, and ship-shaped deep-cavity components [4][5][6] . Since the significant improvement of the new generation equipment for high reliability, long life and light weight, there is an urgent need to replace the traditional multi-piece tailor-welded structure with an integral structure [7] [8] . Such integral thin shell is a kind of large-size curved surface components.…”
Section: Introductionmentioning
confidence: 99%
“…With high strength-to-weight ratio, excellent fracture toughness, and good corrosion resistance [1][2][3] , aluminum alloys have been widely used in the manufacture of curved shell in aviation, aerospace, automotive, and marine fields, such as the bottom of launch vehicle fuel tanks, aircraft skins, body coverings of automotive, and ship-shaped deep-cavity components [4][5][6] . Since the significant improvement of the new generation equipment for high reliability, long life and light weight, there is an urgent need to replace the traditional multi-piece tailor-welded structure with an integral structure [7] [8] . Such integral thin shell is a kind of large-size curved surface components.…”
Section: Introductionmentioning
confidence: 99%
“…When the stretching speed is increased, applying 200 kN tension to the metal material will cause dislocation intensive reduction of the material tensile properties and fracture of the metal material. Yuan and Fan ( 2019 ) found that a reasonable choice of speed and pressure is required when stretching metal materials. When the metal is stretched, this operation needs to ensure that the metal crystal slip is produced and the tensile properties of the material are taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its excellent properties, such as high melting point (3410 ± 10 ℃), high hardness, high thermal conductivity, high temperature strength, low coe cient of thermal expansion and so on [1][2][3], tungsten (W) is widely used in the aerospace, military industry, optical manufacturing, nuclear reactors, medical devices and other elds [4][5][6][7]. For example, in the eld of optical manufacturing, W has become an ideal material for the manufacture of molds for ultra-precise glass parts [8].…”
Section: Introductionmentioning
confidence: 99%